The phenomenon of women who continue to stay in abusive marriages : a case study of selected women in Mankweng Area, Limpopo Province - Mathebula, Wiseman Ntlhari (My University, 2021)
Studies have shown that women abuse in marriages is prevalent. Globally, one in three (1:3) or 35% of women have experienced physical and or sexual violence by an intimate partner who in some instances, could have been a marital partner or spouse. Reports from Statistics South Africa show that one in every four of all women in South Africa is assaulted by their partners weekly. This study sought to describe reasons why women continue to stay in abusive marriages. The study was qualitative in nature and used a case study design. The sampling of the study was purposive and involved sixteen (16) participants who met the criteria of the study: women who continued to stay in abusive marriages. The study was conducted at Khuseleka One-stop Centre and Victim Empowerment Programme in Mankweng, Capricorn District in Limpopo Province. Data was collected using a semi-structured interview guide, and was analysed using Thematic Content Analysis (TCA) to gain in depth account from participants of their abuse in marriage. This study employed the Womanism theory to discuss findings. The major finding of this study was that many abused women who stay on in their marriage are economically dependent on their husbands. The study further reveals that children are main contributing factors that hinder these women from leaving abusive partners. The study further reveals that cultural beliefs play a crucial role since these women were socialised and brought up with cultural beliefs that “lebitla la mosadi ke bogadi”, which simply means that a woman’s grave is at the home of her husband. The study recommends educational programmes about GBV and related programmes for both genders.
Thesis (M. A. ( Social Work)) -- University of Limpopo, 2021
Keywords: Abusive marriage; Mankweng; Women abuse; Violence; Social problems; Women -- Abuse -- South Africa; Family violence -- South Africa; Victims of family violence